Good for whom? Dendeiculture reactions by contract in Amazon paraense - Tavares, Paula Egyto; Mota, Dalva Maria da (Sustainability in Debate, 2020)
This article analyzes the acceptance or resistance of contract oil palm cultivation in Irituia. Research was based on an analysis of documents and secondary data sources, and included 30 interviews with oil palm farmers, a famers’ union member and representatives of the municipal institutions. Research findings show that initial differences regarding the activity remain until today. Those who defend the activity cite the possibilities of improving the quality of life for regional residents; defenders include a group of farmers and state government agents. Critics, those from municipal institutions, argue that oil palm cultivation is not fitting to the local reality and a separate group of farmers absorbed these criticisms and are apprehensive regarding the new activity.